Developing Academic Writing Skills in Art and Design through Blogging - Groppel-Wegener, Alke (Journal of Academic Writing, 2012)
In the creative disciplines of Art and Design, students need to develop the ability to critically assess and put into words what they feel, think and know about their working practices (and by extension their work). The careful development of the transition between knowing instinctively, thinking and writing is well established in the literature (e.g. Schön 1983 and 1987, and Biggs 2004), but only little has been done to integrate this into the Higher Education curriculum using writing as a tool for making the reflection explicit. In order to find out whether exploratory writing in the form of blog posts has the potential to allow Art and Design students to develop their academic practice, a small scale pilot project integrated blogging tasks into introductory modules of four first year undergraduate courses. Student feedback on their experience of blogging, and particularly their perceptions of the value of blogging as exploratory writing, gained through end of module questionnaires is analysed to investigate the potential to use writing to develop their academic practice. Findings indicate that it is the motivation of students that is crucial to allow students to see writing as a thinking process and developmental tool for their practical work, rather than as an unrelated academic outcome.